A comparative study of gallstones from children and adults using FTIR spectroscopy and fluorescence microscopy - Marks Robert S; Polyak Boris; Levi Chen; Kantarovich Keren; Cohen Beny; Huleihel Mahmoud; Ramesh Jagannathan; Kleiner Oleg; Mordehai Jacov; Cohen Zahavi; Mordechai Shaul (BMC Gastroenterology, 2002)
Abstract Background Cholelithiasis is the gallstone disease (GSD) where stones are formed in the gallbladder. The main function of the gallbladder is to concentrate bile by the absorption of water and sodium. GSD has high prevalence among elderly adults. There are three major types of gallstones found in patients, White, Black and Brown. The major chemical component of white stones is cholesterol. Black and brown stones contain different proportions of cholesterol and bilirubin. The pathogenesis of gallstones is not clearly understood. Analysis of the chemical composition of gallstones using various spectroscopic techniques offers clues to the pathogenesis of gallstones. Recent years has seen an increasing trend in the number of cases involving children. The focus of this study is on the analysis of the chemical composition of gallstones from child and adult patients using spectroscopic methods. Methods In this report, we present FTIR spectroscopic studies and fluorescence microscopic analysis of gallstones obtained from 67 adult and 21 child patients. The gallstones were removed during surgical operations at Soroka University Medical Center. Results Our results show that black stones from adults and children are rich in bilirubin. Brown stones are composed of varying amounts of bilirubin and cholesterol. Green stones removed from an adult, which is rare, was found to be composed mainly of cholesterol. Our results also indicated that cholesterol and bilirubin could be the risk factors for gallstone formation in adults and children respectively. Fluorescence micrographs showed that the Ca-bilirubinate was present in all stones in different quantities and however, Cu-bilirubinate was present only in the mixed and black stones. Conclusions Analysis based on FTIR suggest that the composition of black and brown stones from both children and adults are similar. Various layers of the brown stone from adults differ by having varying quantities of cholesterol and calcium carbonate. Ring patterns observed mainly in the green stone using fluorescence microscopy have relevance to the mechanism of the stone formation. Our preliminary study suggests that bilirubin and cholesterol are the main risk factors of gallstone disease.